Simultaneous EEG-fMRI reveals brain networks underlying recognition memory ERP old/new effects - Hoppstädter, Michael; Flor, Herta (NeuroImage, 2015)
The mapping of event-related potentials (ERP) on functional magnetic resonance imaging (fMRI) data remains difficult as scalp electroencephalography (EEG) is assumed to be largely insensitive to deep brain structures. Simultaneous recordings of EEG and fMRI might be helpful in reconciling surface ERPs with hemodynamic activations in medial temporal lobe structures related to recognition memory. EEG and imaging studies provide evidence for two independent processes underlying recognition memory, namely recollection and familiarity. Recollection reflects the conscious retrieval of contextual information about a specific episode, while familiarity refers to an acontextual feeling of knowing. Both processes were related to two spatiotemporally different ERP effects, namely the early mid-frontal old/new effect (familiarity) and the late parietal old new effect (recollection). We conducted an exploratory simultaneous EEG-fMRI study using a recognition memory paradigm to investigate which brain activations are modulated in relation to the ERP old/new effects. To this end we examined 17 participants in a yes/no recognition task with word stimuli. Single-trial amplitudes of ERP old/new effects were related to the hemodynamic signal in an EEG-informed fMRI analysis for a subset of 12 subjects. FMRI activation in the right dorsolateral prefrontal cortex and the right intraparietal sulcus was associated with the amplitude of the early frontal old/new effect (350-550ms), and activation in the right posterior hippocampus, parahippocampal cortex and retrosplenial cortex was associated with the amplitude of the late parietal old new effect (580-750ms). These results provide the first direct link between electrophysiological and hemodynamic correlates of familiarity and recollection. Moreover, these findings in healthy subjects complement data from intracranial ERP recordings in epilepsy patients and lesion studies in hypoxia patients.
Gesehen am 15.02.2018